2020
DOI: 10.1097/olq.0000000000001187
|View full text |Cite
|
Sign up to set email alerts
|

Trends in Human Immunodeficiency Virus and Sexually Transmitted Infection Testing Among Gay, Bisexual, and Other Men Who Have Sex With Men After Rapid Scale-up of Preexposure Prophylaxis in Victoria, Australia

Abstract: Objective Scale-up of human immunodeficiency virus (HIV) preexposure prophylaxis (PrEP) has raised concerns regarding its impact on clinic capacity and access to HIV testing. We describe enrolment in PrEPX, a large PrEP implementation study in Victoria, Australia, and the impact of PrEP uptake and maintenance on existing health services. Methods We describe enrolment between July 26, 2016, and March 31, 2018, and trends in HIV testing among PrEPX partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…These findings may reflect the growing need for large‐scale PrEP programmes with integrated, comprehensive care. Our study findings are in line with those of two PrEP implementation studies conducted in Australia that showed widespread interest, rapid enrolment, and high retention among gay, bisexual and other MSM [ 24 , 25 ]. The high participation and retention at first follow‐up might also be related to the innovative design of the questionnaires used in the SwissPrEPared programme, which consisted of self‐reported data collected through online, self‐administered questionnaires compatible with smartphones.…”
Section: Discussionsupporting
confidence: 90%
“…These findings may reflect the growing need for large‐scale PrEP programmes with integrated, comprehensive care. Our study findings are in line with those of two PrEP implementation studies conducted in Australia that showed widespread interest, rapid enrolment, and high retention among gay, bisexual and other MSM [ 24 , 25 ]. The high participation and retention at first follow‐up might also be related to the innovative design of the questionnaires used in the SwissPrEPared programme, which consisted of self‐reported data collected through online, self‐administered questionnaires compatible with smartphones.…”
Section: Discussionsupporting
confidence: 90%
“…The opportunities for more effective prevention of new HIV infections have expanded over the past decade. Oral pre-exposure prophylaxis (PrEP) has been demonstrated to be highly efficacious and often effective in public health practice [8][9][10]. Two monthly injections of a long-acting formulation of cabotegravir have been demonstrated in clinical trials to be more effective than oral PrEP [11,12].…”
Section: Hiv Prevention Has Changedmentioning
confidence: 99%
“…24 Internationally, discontinuation of PrEP has been associated with younger age, 25–27 minority ethnic status, 27,28 financial barriers, 29 and drug use. 25,26 However, as many people do appear to stop or pause their PrEP use in line with periods of lower risk, 30,31 more research is needed to determine ways to identify patients who are more likely to discontinue PrEP and subsequently engage in risk behavior. This issue has become especially pertinent in the context of the COVID-19 pandemic, during which many GBM ceased taking PrEP while physical distancing restrictions were in effect.…”
Section: Discussionmentioning
confidence: 99%